Telemedicina, un aporte universitario - Zomosa R., Gustavo (Revista Hospital Clínico Universidad de Chile, 2015)
The delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, research and evaluation, and for the continuing education of health care providers, all in the interests of advancing the health of individuals and their communities”(OMS)(1) TM has been reported since 50 years(2) and recent developments like internet and transition and storage standards of digital imaging: DICOM(3) allowed to develop Teleradiology (TR) leading TM modality.TR consists in transformation, acquisition, storage of digital imaging and transmition at high speed to high resolution work stations to allow distant radiological diagnosis(4). Chilean TR experience begins in 1995(5) and the Chilean Health Minister has called to 4 public tenders in CT Scan reports since 2012(7,8). In 2015 the Faculty of Medicine created the Informatic and TM Center (CIMT) to work with the University of Chile Clinic Hospital (HCUCH) in TM, TR and telepsiquiatry, teledermatology, telecardiology, telemonitoring and specialist assistance. A contribution in the HCUCH-TR development is the study of the factors involved in its success by the HOT-fit evaluation model(11).